The Conservation of a Mummified Child from the Australian Institute of Archaeology - Jones-Amin, Holly; Mucic, Marica (Buried History: The Journal of the Australian Institute of Archaeology, 2022)
The paper discusses a child mummy’s past restoration, pre-treatment condition, and the minimally invasive conservation interventions undertaken. The mummy was purchased in 1965 by the Australian Institute of Archaeology and has been displayed and stored since that time. Conservation was made possible by a grant. Images taken soon after the mummy arrived in Australia guided some conservation decisions. Analytical methods used to identify materials associated with previous restorations and the mummy’s deteriorating condition included Fourier transform infrared spectroscopy, Energy-dispersive X-ray spectroscopy fluorescence and Reflectance Transformation Imaging.